Quantitative real-time PCR analysis of Anopheles dirus TEP1 and NOS during Plasmodium berghei infection, using three reference genes - Liew, Jonathan Wee Kent; Fong, Mun Yik; Lau, Yee Ling (PeerJ, 2017)
Quantitative reverse transcription PCR (qRT-PCR) has been an integral part of char- acterizing the immunity of Anopheles mosquitoes towards Plasmodium invasion. Two anti-Plasmodium factors of Anopheles, thioester-containing protein 1 (TEP1) and nitric oxide synthase (NOS), play a role in the refractoriness of Anopheles towards Plasmodium infection and are generally expressed during infection. However, these are less studied in Anopheles dirus, a dominant malaria vector in Southeast Asia. Furthermore, most studies used a single reference gene for normalization during gene expression analysis without proper validation. This may lead to erroneous quantification of expression levels. Therefore, the present study characterized and investigated the expression profiles of TEP1 and NOS of Anopheles dirus during P. berghei infection. Prior to that, the elongation factor 1-alpha (EF1), actin 1 (Act ) and ribosomal protein S7 (S7) genes were validated for their suitability as a set of reference genes. TEP1 and NOS expressions in An. dirus were found to be significantly induced after P. berghei infection.